Testing software and systems : 28th IFIP WG 6.1 International Conference, ICTSS 2016, Graz, Austria, October 17-19, 2016, Proceedings /: 28th IFIP WG 6.1 International Conference, ICTSS 2016, Graz, Austria, October 17-19, 2016, Proceedings. (2016) - Unknown
No abstract available